The burden of depression, anxiety and schizophrenia among the older population in ageing and aged countries: an analysis of the Global Burden of Disease Study 2019 - Wu Hong; Ying Cheng; Yu Fang; Jinxin Zheng; Shiyang Guan; Meiti Wang (General Psychiatry)
Background Depression, anxiety and schizophrenia among older persons have become global public health challenges. However, the burden of these disorders in ageing and aged countries has not been analysed.Aims To investigate the burden of depression, anxiety and schizophrenia among older adults in ageing and aged countries.Methods Using data from the Global Burden of Disease Study 2019, we calculated the estimated annual percentage change (EAPC) in the age-standardised incidence rates (ASIR) and age-standardised disability-adjusted life years (DALYs) rates (ASDR) for depression, anxiety and schizophrenia of older people in ageing countries (China, India, Indonesia) and aged countries (Japan, Italy, Portugal) between 1990 and 2019. Trends in incidence and DALYs were analysed by gender and age.Results In 2019, the highest incidence of depression, anxiety and schizophrenia in the older population in aged countries was in Japan (927 271.3 (752 552.3–1 125 796.5), 51 498.2 (37 625.7–70 487.3) and 126.0 (61.0–223.2), respectively), while the highest incidence in ageing countries was in China (5 797 556.9 (4 599 403.4–7 133 006.5), 330 256.1 (246 448.9–445 987.4) and 1067.7 (556.2–1775.9), respectively). DALYs for these disorders were similar, with the highest in Japan and China. From 1990 to 2019, the ASIR for depressive disorders decreased in aged countries but increased in ageing countries; the ASIR for anxiety disorders and schizophrenia declined in both ageing and aged countries. The ASDR for depressive disorders was consistent with the ASIR but not for anxiety disorders and schizophrenia. The ASIR for depressive disorders was higher in older women, while the opposite was observed in anxiety disorders and schizophrenia. Notably, the conditions of burden of depressive disorders, anxiety disorders and schizophrenia in the 65–70-year-old age group were the most burdensome.Conclusions The incidence and DALYs of these three mental disorders increased while exhibiting differences between ageing and aged countries. Raising awareness about formulating health policies for preventing and treating mental disorders in the older population is necessary to reduce the future burden posed by the ageing challenge.